Effect of root canal status on periodontal healing after surgical injury in dogs. - Holland, R.; Otoboni Filho, José Arlindo [UNESP]; Bernabé, P. F.; Nery, Mauro Juvenal [UNESP]; Souza, V. de; Berbert, A. (Munksgaard Int Publ Ltd, 1994)
This study was carried out to observe if the status of the root canal might influence the healing process of surgically prepared experimental periodontal lesions. Forty tooth roots from four dogs were divided into four different groups: a) root canals with vital pulps, b) root canals open to the oral environment, c) root canals infected and filled with zinc oxide eugenol cement, and d) root canals infected and filled with calcium hydroxide. By means of a surgical intervention, a cavity was prepared in the medium portion of the roots. Six months later, the specimens were removed and prepared for histological analysis. The results, which were submitted to statistical analysis, showed that the status of the root canals influenced the healing process of the experimental periodontal lesions. In the groups where the root canals were filled, calcium hydroxide gave the best results. In the group with root canals left open to the oral environment, resorption of the dentin of the experimental cavities, was the most obvious observation. However, it did not prevent the repair process, only slowed it down.
Keywords: Calcium hydroxide; Root canal filling material; Zinc oxide eugenol; Analysis of variance; Animal; Cementum; Comparative study; Dog; Drug effect; Endodontics; Pathophysiology; Periodontal disease; Periodontal ligament; Physiology; Tooth pulp; Tooth pulp disease; Wound healing; Analysis of Variance; Animal; Calcium Hydroxide; Comparative Study; Dental Cementum; Dental Pulp Cavity; Dentin, Secondary; Dogs; Periodontal Diseases; Periodontal Ligament; Root Canal Filling Materials; Root Canal Therapy; Wound Healing; Zinc Oxide-Eugenol Cement